Pelan pembangunan bank dunia di negara-negara Islam: ketidakadilan dari perspektif bantuan asing dan penswastaan projek air bersih - Salawati Mat Basir (Fakulti Undang - Undang, 2010)
Many Muslim countries face challenges of massive poverty, slow GDP, low level of education and insufficient public health systems. The governments in these countries do not have sufficient capital resources to eradicate poverty and prevent deaths from preventable causes. Hence, the World Bank together with developed countries have been providing financial assistance to majority Muslim countries for over half a century in an attempt to improve living conditions of the people. However, this paper attempts to explore unfairness of foreign aid on a Muslim country’s overall including on political institutions. Secondly, this paper presents a discussion on how the World Bank prescribes water privatisation and full recovery cost as conditions for their loans to Muslim country governments for the creation and expansion of clean water. Finally, this paper unveils how unfairness of the World Bank development plan to many Muslim countries and why Islamic Development Bank (IDB) must take an urgent action to overcome these problems